Honor related violence: a new social psychological perspective - Ermers, Robert (Routledge, Taylor & Francis Group, 2018)
The context of this book -- Approaches to the study of honour -- Dishonour and stigma -- Violence and stigma -- Blood revenge -- Honour killing -- Conclusions -- Index -- Bibliography